Corporate Social and Financial Performance in Chemical Industry in the United States - Md. Jahidur Rahman; Yuyang Luo (Indonesian Management and Accounting Research, 2020)
The purpose of this study is to investigate the relationship between corporation financial performance (CFP) and corporate social performance (CSP). This study uses return on assets (ROA) to measure corporate financial performance. We use two different measurement strategies independently to measure corporate social performance: (a) KLD index as perceptual CSP measure strategy; (b) Percentage change in waste produced by the corporation (TRI index) as behavior CSP measure strategy. Using the sample of 123 U.S chemical firms from 2009-2018, this paper finds that KLD index has a significantly positive association with CFP, while TRI index is not significantly associated with CFP. Meanwhile, this paper also finds that seven individual dimensions of CSP are significantly related to CFP except for the environment dimension. The result expands the importance of CSP measurement methods from cross-industry research to single industry research and contributes to the CSP individual dimensions literature.